Prior experience with cardiovascular medicines predicted longer persistence in people initiated to combinations of antihypertensive and lipid-lowering therapies: findings from two Australian cohorts - Bartlett, Louise E (Patient Prefer Adherence, 2018)
PURPOSE: Many studies of persistence involving fixed dose combinations (FDCs) of cardiovascular medicines have not adequately accounted for a user’s prior experience with similar medicines. The aim of this research was to assess the effect of prior medicine experience on persistence to combination therapy. PATIENTS AND METHODS: Two retrospective cohort studies were conducted in the complete Pharmaceutical Benefits Scheme prescription claims dataset. Initiation and cessation rates were determined for combinations of: ezetimibe/statin; and amlodipine/statin. Initiators to combinations of these medicines between April and September 2013 were classified according to prescriptions dispensed in the prior 12 months as either: experienced to statin or calcium channel blocker (CCB); or naïve to both classes of medicines. Cohorts were stratified according to formulation initiated: FDC or separate pill combinations (SPC). Cessation of therapy over 12 months was determined using Kaplan–Meier survival analysis. Risk of cessation, adjusted for differences in patient characteristics was assessed using Cox proportional hazard models. RESULTS: There were 12,169 people who initiated combinations of ezetimibe/statin; and 26,848 initiated combinations of amlodipine/statin. A significant proportion of each cohort were naïve initiators: ezetimibe/statin cohort, 1,964 (16.1%) of whom 81.9% initiated a FDC; and amlodipine/statin cohort, 5,022 (18.7%) of whom 55.4% initiated a FDC. Naïve initiators had a significantly higher risk of ceasing therapy than experienced initiators regardless of formulation initiated: ezetimibe/statin cohort, naïve FDC versus experienced FDC HR=3.0 (95% CI 2.8, 3.3) and naïve SPC versus experienced SPC HR=4.4 (95% CI 3.8, 5.2); and amlodipine/statin cohort naïve FDC versus experienced FDC HR=2.0 (95% CI 1.8, 2.2) and naïve SPC versus experienced SPC HR=1.5 (95% CI 1.4, 1.6). CONCLUSION: Prescribers are initiating people to combinations of two cardiovascular medicines without prior experience to at least one medicine in the combination. This is associated with a higher risk of ceasing therapy than when combination therapy is initiated following experience with one component medicine. The use of FDC products does not overcome this risk.